2022
DOI: 10.3390/vaccines10030412
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 Vaccinations among a State-Wide Year-Long Surveillance Initiative in a Conservative Southern State

Abstract: By the end of 2021, the COVID-19 pandemic resulted in over 54 million cases and more than 800,000 deaths in the United States, and over 350 million cases and more than 5 million deaths worldwide. The uniqueness and gravity of this pandemic have been reflected in the public health guidelines poorly received by a growing subset of the United States population. These poorly received guidelines, including vaccine receipt, are a highly complex psychosocial issue, and have impacted the successful prevention of disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Moreover, availability of the vaccine began in mid-January for individuals aged 70 or older, which likely also impacted testing demand. At the time of the survey, 58.7% (4213/7170) of respondents had ever been tested for COVID-19, whereas it has previously been reported that 66.7% received the vaccine, suggesting the possibility that a number of respondents did not actively seek testing due to fear of exposure [ 23 ]. Our results show the likelihood of test positivity was highest among Black/African Americans and older individuals (aged ≥50 years).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, availability of the vaccine began in mid-January for individuals aged 70 or older, which likely also impacted testing demand. At the time of the survey, 58.7% (4213/7170) of respondents had ever been tested for COVID-19, whereas it has previously been reported that 66.7% received the vaccine, suggesting the possibility that a number of respondents did not actively seek testing due to fear of exposure [ 23 ]. Our results show the likelihood of test positivity was highest among Black/African Americans and older individuals (aged ≥50 years).…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have used survival (time‐to‐event) analysis as it relates to vaccine effectiveness and hesitancy, this study is unique in that it assessed time to vaccine uptake by using actual COVID‐19 vaccination dates, conducting analyses based on date of vaccine eligibility in DC, and verifying dates using a jurisdictional immunization registry 25,42 . Due to the point in time of the study, obtaining vaccination information was easy and non‐intrusive.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have used survival (time-toevent) analysis as it relates to vaccine effectiveness and hesitancy, this study is unique in that it assessed time to vaccine uptake by using actual COVID-19 vaccination dates, conducting analyses based on date of vaccine eligibility in DC, and verifying dates using a jurisdictional immunization registry. 25,42 Due to the point in time of the study, obtaining vaccination information was easy and non-intrusive. We found that most participants had COVID-19 vaccination cards readily available since vaccination was required to participate in activities dining at restaurants, attending a performance, or traveling by air at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Mass vaccination programs were an essential strategy to tackle the spread of SARS-CoV-2 and reduce severe forms of COVID-19, allowing for total social and economic activity [ 2 , 3 , 5 , 7 , 8 , 9 , 10 ]. However, one of the potential threats to this goal was vaccine hesitancy [ 3 , 5 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, vulnerable pockets of unvaccinated people might remain since unvaccinated individuals may cluster together [ 6 , 10 , 12 , 26 ]. With the plateauing of vaccination uptake rates and the emergence of new variants, it is fundamental to identify, characterize, and monitor clusters of the population that remain hesitant, due to the risk of community transmission remaining active in these groups [ 3 , 9 , 10 , 12 , 23 , 27 ]. Being a migrant or living in a socially deprived setting has been associated with a lower vaccine uptake because of hesitancy or lack of access [ 5 , 9 , 12 , 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%